A study on ground reality of freshwater fish farming in biofloc tank in West Bengal, India - Mali, Prasenjit; Ghosh, Swagat; Dash, Gadadhar; Jawahar, T.; Chowdhury, Supratim; Das, Sudhir Kumar (Journal of the Inland Fisheries Society of India, 2022)
Introduction of land-based biofloc technology has brought huge changes in concept of fish farming. The practice of biofloc farming is gaining popularity amidst COVID-19 situation. For the present study on biofloc tank farming in West Bengal, 110 biofloc farmers who had harvested at least one crop, were selected through simple random sampling method, from a list of 390 biofloc farmers from 13 districts of West Bengal. Data were collected from the selected respondents during the last quarter of 2020, according to a structured interview schedule on every minute aspect on culture strategies, technical issues, profit gain and prospect. Oreochromis niloticus was found to be the most cultured species followed by Anabas cobojius, Catfishes Heteropneustes fossilis and Clarias batrachus, Pangasianodon hypophthalmus and Labeo bata. Majorities of the respondents were found young, educated, least experienced and small scale investors. Disease outbreaks and mass mortalities were found very common to all. Disease prevention strategies and therapeutic measurements were found quite unsatisfactory. Most respondents failed to achieve their expected profit. Only 13.6% farmers were found to be highly satisfied, whereas, 62.7% were dissatisfied but continue the culture and 23.7% were highly disappointed. Synchronizing C:N ratio with microbial dynamics by the famers was found to be the major gap in technical knowhow.Â Key words Biofloc culture, Freshwater fish, West Bengal